On the transition from partial wetting to complete wetting of methanol on graphite. Issue 47 (25th November 2019) - Prasetyo, Luisa; Horikawa, Toshihide; Takashima, Naoki; Do, D. D.; Nicholson, D.
Abstract : Excellent agreement with experiment for methanol adsorption on graphitized carbon black at low temperatures by Monte Carlo simulation. Incomplete wetting and complete wetting are observed at a range of temperatures above the triple point. Abstract : The transition from partial wetting to complete wetting for methanol adsorbed on a highly graphitized thermal carbon black, Carbopack F, over a range of temperature from the triple point at 185 K to 298 K, was investigated using Monte Carlo simulation and high-resolution experiments. At 190 K, (above the triple point) both the experimental and simulated adsorption isotherms cut the P / P 0 axis at a finite loading; a feature of partial wetting that has not been recognized previously in the literature. This occurs because most O- and H-atoms in the second layer of the adsorbate point towards the adsorbent surface to form hydrogen bonds with molecules in the first layer and therefore the interface between the bilayer adsorbed film and the gas phase consists mainly of methyl groups, preventing the system from forming higher layers. At temperatures above 263 K, methanol adsorption increases with pressure and wets the surface as the pressure approaches the bulk coexistence pressure P 0 . This is because the O–H and O–CH3 bonds of methanol in the region above the second layer have random orientation, and adsorption in higher layers takes place via hydrogen bonding. From extensive simulations of methanol adsorption on adsorbents of different strength over a wide temperature range, a parametric map has been constructed which identifies the regions of non-wetting, partial wetting and complete wetting. For a given surface strength, wetting is favoured at higher temperatures, and at a given temperature there is a transition from non-wetting on weakly adsorbing substrates to either partial wetting or to complete wetting on strong adsorbents at temperatures below or above the roughening temperature T r of 260 K.